Mandibular unilateral fusion in primary dentition - Neena Eregowda; Shruti Singh; P Poornima; K B Roopa (Wolters Kluwer Medknow Publications, 2017)
Fusion is a developmental anomaly which occurs due to a union of one or more adjacent teeth during morphodifferentiation of the dental germs. The prevalence of tooth fusion is estimated at 0.5%-2.5% in the primary dentition. These anomalies may be unilateral or bilateral and may affect either dentition although the deciduous teeth are more commonly affected. Early diagnosis of such condition is important because it may cause clinical problems, such as esthetic concerns, and caries. This report describes a case of unilateral fusion of the primary mandibular lateral incisor and canine and aims to evaluate any associated pathology.